Нестационарное деформирование упругого слоя при смешанных граничных условиях - Кубенко, В.Д. (Прикладная механика, 2016)
Побудовано аналітичний розв'язок плоскої задачі про дію нестаціонарного навантаження на поверхню пружного шару за умов змішаної крайової задачі: на одній границі задані нормальне напруження і дотичне переміщення (четверта крайова задача теорії пружності), на іншій - нормальне переміщення і дотичне напруження (друга крайова задача). Застосовано інтегральні перетворення Лапласа і Фур'є. Обернення інтегральних перетворень виконано точно за допомогою табличних співвідношень і теорем про згортки для різноманітного асортименту діючих нестаціонарних навантажень. Вирази для напруження і переміщення одержано в явному аналітичному виді. Конкретно розглянуто навантаження, прикладене до області постійних розмірів і до області, розміри якої змінюються за заданим законом. Виконані обчислення демонструють розвиток нормального напруження залежно від часу та просторових координат. Проаналізовано характерні особливості хвильових процесів. An exact analytical solution is constructed for the plane problem on action of non-stationary load over the surface of elastic layer. The mixed boundary problem is considered, when the normal stress and tangential displacement are given on one side of layer (the fourth boundary problem of the theory of elasticity) and the tangential stress and normal displacement are given on another side of layer (the second boundary problem of the theory of elasticity). The Laplace and Fourier integral transforms are applied. The Laplace and Fourier inversions are carried out exactly using the tabulated values and convolution theorems for diverse assortment of acting non-stationary loads. The expressions for stresses and displacements are obtained in the explicit analytical form. The load is considered particularly, when it is applied over the area of constant sizes and changing by the given law sizes. The carried out computing demonstrates the progress of normal stress in dependence on time and spatial coordinates. The peculiarities of wave processes are analyzed.